Phnom Penh ou l’ordre métropolitain : polices, pouvoirs et territoires - Gabriel Fauveaud (EchoGéo)
In this article, I propose a critical analysis of the Phnom Penh metropolization process by investigating practices and strategies of local police forces. Firstly, I argue that the metropolization process is based on a particular political and economic ordering of the city’s territories, the “ordopolis”. Secondly, I argue that strategies and practices of local police forces rely on different forms of “urban disorders”, which support a rent-seeking police economy. In conclusion, we will see that the metropolitan order has been recently the subject of a “reciprocal territorialization”, which means a renewal of the urban centrality.